Research Trends in E-Procurement and Goods/Services Procurement: A Bibliometric Study with Insights from Indonesia (2020–2025) - Santosa, Dewa Puji; Pramesti, Nectaria Putri (Civil and Sustainable Urban Engineering, 2025)
The rapid evolution of procurement systems, particularly through digital platforms, transformed how goods and services were acquired in both public and private sectors. Driven by technological advances, regulatory reforms, and lessons learned from implementation challenges, procurement research expanded significantly in recent years. This study aimed to map research trends in e-procurement and goods/services procurement between 2020 and 2025, with specific insights from Indonesia as one of the leading contributors. A bibliometric approach was employed using VOSviewer to analyze 136 articles retrieved from the Scopus, Google Scholar, and Garuda databases. Metadata, including titles, authors, keywords, and citations, were systematically processed to identify publication networks, keyword clusters, and thematic evolution. The results revealed that Indonesia led in publication volume, followed by countries such as Kenya, the United States, and the United Kingdom. Keyword mapping highlighted dominant themes of performance, cost efficiency, and procurement practices, while emerging topics since 2023 included digital platforms, open contracting, and transparency. Author collaboration remained fragmented, with limited international networking. The analysis also indicated a gradual shift from procedural issues toward multidimensional concerns, integrating technical, managerial, and social perspectives in procurement research. This study concluded that bibliometric mapping provided valuable insights into the current state and future directions of procurement research. It recommended further comparative studies across regions, greater focus on user satisfaction and sustainability, and the strengthening of international collaboration to broaden the knowledge base.